PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCH UNTUK MENGKAJI SELF-CONFIDENCE DAN PENINGKATAN KEMAMPUAN KOMUNIKASI MATEMATIS - Rina Asvia Wadviroh; Rianti Cahyani; Sidiq Aulia Rahman (Universitas Islam Nusantara, 2022)
This research was motivated by the low mathematical communication skills and lack of students' self-confidence in learning mathematics. One alternative learning that can be applied to improve students' mathematical communication skills is the Make a Match cooperative learning model. The purpose of this study was determine self-confidence and improve mathematical communication skills of junior high school students. The research method used in this study was a quasi-experimental method with Nonequivalent Pretest-posttest Control Group Design. This research was conducted at a junior high school in Bandung Regency. The research sample was students of class VII-B as the experimental class and class VII-C as the control class. The experimental class uses the make a match type cooperative model, while the control class uses the discovery learning model. The instrument used was a test of mathematical communication skills, a confidence questionnaire and an observation sheet of educator learning activities. The results of the study were analyzed using t-test. Based on the results of the analysis, it can be concluded that the self-confidence of the two classes had a very good interpretation. Meanwhile, mathematical communication skills of students whose learning using the make a match type cooperative model was better than mathematical communication skills of students whose learning uses discovery learning models.